Consumer Preferences for Dehydrated Vegetables - , Anupama Verma, Rishabh Patidar, P. Shrivastava (Archives of Current Research International, 2024)
Why do buyers purchase certain products but not others? How do they determine how much to purchase? Under what circumstances does a sensible customer spend his money and what is his goal? These are some of the important questions to which we seek answers. The overall vegetable production for 2023-24 is expected to be around 205.80 million tonnes, screening a balanced trend. Substantial growths are expected in crops like tomato, cabbage, cauliflower, tapioca, bottle gourd, pumpkin and cucumber. Globally, it has been estimated that 42% of all of fruit and vegetable calories produced are ultimately wasted. Our sample consisted of a total of 100 participants who have been consuming the dehydrated vegetables. The study was conducted in the year 2023-24. Our focus in the physical sampling exercise was on important locations around Jabalpur, MP. Due to the location VAM Agro, selection of Jabalpur, Madhya Pradesh as study area for examining scope of dehydrated vegetables with specific reference to VAM Agro Processing Private Limited was therefore quite strategic and justified. We relied on convenient sampling in picking the study participants. It was found that more male members are there in the dehydrated vegetable consumer group in comparison with females. Of the major proportion of consumers interested in dehydrated vegetables, 78% fall within the age bracket of 21-25 years. 40 per cent of the respondents use them in instant foods such as potato chips and ready-to-eat foods, citing convenience and speed. A cool, dry place was best preferred by most consumers for storing their dehydrated vegetables, as it allows quality maintenance and prevents spoilage from moisture.